Strategies for Effective Plankton Management in Kijing Taiwanese (Anodonta woodiana, Lea): A Study on Stocking Density and Aquaculture Techniques - Rema Apria Ningrum; Moh Awaludin Adam; Nanda Diniarti; Yulia Dewi Anjani; Irfan Maulana (Indonesian Society of Limnology, 2024)
Understanding the dynamics of plankton in Kijing Taiwanese (Anodonta woodiana, Lea) cultivation is crucial for optimizing growth performance. This study aims to investigate the influence of stocking density and cultivation methods on the daily population dynamics of plankton in Kijing Taiwanese aquaculture. The experimental study tested different stocking densities in cultivation ponds, namely 5, 10, and 15 ind/m2. Descriptive analysis was employed to interpret the data obtained. The results indicate that Kijing Taiwanese absorb approximately 40 liters/day of water with particle sizes ranging from 0.1 to 5.0 µm, achieving 100% and 99.5% filtration for particles > 4.0 µm and organic matter, respectively. Various class of plankton were identified in the cultivation ponds, including Bacillariophyceae, Chlorophyceae, Cyanophyceae, Dinophyceae, Euglenophyta, and Pyrophyta, with abundances ranging from 2000-68000 ind/cell. The study observed an increase in plankton abundance by approximately 700-2000 ind/cells daily. Water quality measurements revealed pH 7.4, temperature 29.4°C, TDS 92.3 mg/L, turbidity 9-45 NTU, BOD 1-3, DO 5 mg/L, and phosphate (PO4) 0.3 mg/L. This research concludes that there is an influence between kijing stocking density and plankton population density. The interactions that occur are significantly different, because there are significant differences. The higher the distribution density of kijing, the lower the plankton population in the cultivation pond. Further research is recommended to explore the correlation between the abundance of specific plankton types and the growth of Kijing Taiwanese, considering nutrient elements.